Anti-viral activity of blue chanterelle (Polyozellus multiplex) that inhibits α-glucosidase - Lee, Doseung; Boo, Kyung Hwan; Lee, Jin-Man; Unno, Tatsuya; Lee, Wang Shik; Cho, Moonjae; Riu, Key Zung; Lee, Dong-Sun (Food science and biotechnology, 2013)
Blue chanterelle ( Polyozellus multiplex ), known as an edible mushroom, was extracted using methanol to screen on anti-viral agent. Syncytium formation in Newcastle disease virus (NDV)-infected baby hamster kidney (BHK) cell originates from the trafficking of viral glycoprotein into cell-surface. Blue chanterelle inhibited not only syncytium formation, but also trafficking of glycoprotein, hemagglutinin-neuramidase (HN), onto cell-surface. Viral glycoprotein is processed within the endoplasmic reticulum during routing to surface. Blue chanterelle extracts showed the inhibitory activities (IC 50 10 μg/mL) against α-glucosidase. These results suggested that blue chanterelle extracts inhibited the cell-surface expression of NDV-HN glycoprotein without significantly affecting HN glycoprotein synthesis in NDV-infected BHK cells.